The impact of EC membership on Portugal and Spain - C. J. Redston (Intereconomics, 1983)
While the case for Spanish and Portuguese EC membership is largely political, for membership to be a political success it must also be an economic success. Indeed it is economic factors which have ensured that six years after the applications were made, negotiations have not been concluded and that the target date of membership by January 1, 1984, will not be met. What will be the impact of EC membership on the applicants' economies?
Keywords: 330; EC